EP.FRI.472Building the 'LIEGS' way – Establishing an ambulatory Rapid Access Theatre Service for those patients with acute surgical pathology requiring operative management. (28th October 2021) - Amtul, Nasira; Ahmad, Aman; Mutyavaviri, Lindsay; Peckham-Cooper, Adam; Toogood, Giles; Smith, Andrew
Abstract: Aim: LTHT is the largest acute surgical unit in the UK and has seen an annual 11% increase in attendances with often 90 patients assessed daily. 40% patients present with acute biliary pathology but despite this there has been no dedicated operating list for this cohort of patients. Rapid Access Theatre (RAT) lists were created to manage these patients. We report our early results. Method: In October 2020 the trust appointed four EGS Consultants forming a dedicated acute general surgical service. Emphasis was placed on creating ambulatory pathways and those patients safe to be managed at home but requiring surgical intervention are placed on a day case RAT list. COVID-19 has restricted the broad use of this service for all emergency admissions but biliary pathology continues to be amenable to these pathways. Data was collected retrospectively using in-house coding and electronic patient database systems. Results: 34 day case laparoscopic cholecystectomies were performed in the first 10 weeks. Mean age was 44(17-67) with a male:female ratio of 1:1. Mean wait time from clinical review to theatre was 11(3-23) days. 1 patient required overnight admission but there were no readmissions and no reported complications at 30 days. Conclusion: Despite isolation restrictions resulting from COVID-19, the service has allowed patients to be assessed and treated in a timely, safe fashion. The new service has resulted in significant reductions in bed stays and improved patient experiences. Financial savings have been clearly delineated and as such expansion of the model is underway.